Perturbações das equações de Einstein-Boltzmann e suas aplicações à radiação cósmica de fundo - Barros, Gustavo de (2006)
Study aimed at understanding the basics of the new and growing topic of cosmic microwave background (CMB) physics. We present the fundamental concepts, principles and results related with this problem. Since the relevant equations are essentially the Einstein-Boltzmann perturbed equations, a great part of this work is dedicated to these linearized equations, in the conformal Newtonian gauge, with vanishing tri-curvature, for scalar perturbations only. The initial conditions are also touched on. Another part of paramount importance is the application to the description of the power spectrum of temperature anisotropies.